Implementation of Home Visits by Cadres Through Multi-Party Collaboration in the Transformation of Primary Health Services - Dani Ferdian; Ede Surya Darmawan; Arida Bitanajsha Zuqriefa; Christine Pepah; Spiritual Simbolon; Yayan Nuryawan; Rohman Hikmat (GLOBAL HEALTH SCIENCE GROUP, 2026)
The transformation of primary health care services in Indonesia, which began in August 2023, emphasizes improving access, quality, and coverage of health services for all life cycles, including through home visits conducted by Posyandu cadres. However, the implementation of home visits often encounters obstacles, such as lack of knowledge of cadres and limited resources. This study evaluates good practices in implementing home visits by cadres through a multi-party collaboration scheme in the transformation of primary health care services in South Tapanuli. This study employed an action research design to evaluate the implementation of home visits by Posyandu cadres through multi-party collaboration in South Tapanuli. A total of 1,095 families (4,293 community members) across six villages were included in the study using total sampling, ensuring all families in the target villages participated. Data were collected by cadres during home visits using standard forms and included health indicators for pregnant women, postpartum mothers, infants, adolescents, adults, and the elderly. Collected data were entered into a system and analyzed using descriptive statistics to map coverage gaps and identify unmet health service needs. This study was conducted in six villages in South Tapanuli and covered 1,095 families with a total of 4,293 community members over a three-month period (June-August 2024). The results show a mapping of significant health problems in various population groups, such as missing services for pregnant women (incomplete antenatal care of 89.29%), postpartum mothers (not taking vitamin A of 16.67%), infants aged 0-6 months (not doing complete neonatal visits of 32.08%), infants aged 6-72 months (not immunized of 68.16%), adolescents (not doing non-communicable disease screening of 96.91%), and adult and elderly age groups not doing hypertension screening of 77.1% and not doing diabetes screening of 87.9%. This multi-party collaboration has proven effective in identifying and mapping health problems that need to be followed up to reduce the health burden in South Tapanuli.